Medicine through time : essays and dissertations of the Scottish Royal Medical Society, 1751-1970. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2009)
This collection contains over two hundred historical dissertations and essays submitted to the Royal Medical Society between the period 1751-1970. The Royal Medical Society was founded by students of the University of Edinburgh in 1737 and granted a Royal Charter in 1778. The Royal Medical Society boasts some of the most important medical alumni in the world and is widely regarded for its contribution to the medical field. Subjects covered in these essays and dissertations range from the study of psychology and mental health to the treatment of rare bacterial diseases. Thus, the files offer a unique insight into how medical knowledge has changed and evolved over the years.
Date range: 1751-1970.
Keywords: Medicine